2013
DOI: 10.1016/j.asjsur.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

GPC-1 may serve as a predictor of perineural invasion and a prognosticator of survival in pancreatic cancer

Abstract: GPC-1 is significantly related to the perineural invasion of pancreatic cancer, holding some prognostic significance in patients with pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 20 publications
4
57
1
Order By: Relevance
“…Another important clinical use could be the prediction of survival of PC patients, indeed Melo and associates, using a Cox multivariate regression analysis documented that the decrease of circulating GPC1 exosomes as an independent prognostic marker predictive for disease-specific survival. This result confirms previous finding by Duan and coauthors, who reported that GPC1 is significantly related to the perineural invasion in PC and it has an independent prognostic effect on the overall survivals (36).…”
Section: Commentarysupporting
confidence: 93%
“…Another important clinical use could be the prediction of survival of PC patients, indeed Melo and associates, using a Cox multivariate regression analysis documented that the decrease of circulating GPC1 exosomes as an independent prognostic marker predictive for disease-specific survival. This result confirms previous finding by Duan and coauthors, who reported that GPC1 is significantly related to the perineural invasion in PC and it has an independent prognostic effect on the overall survivals (36).…”
Section: Commentarysupporting
confidence: 93%
“…Importantly, anti‐GPC1 mAb also induced potent tumor growth inhibition in xenograft models using patient‐derived GPC1‐positive ESCC tumors, suggesting that GPC1 would be a promising therapeutic target in ESCC. Elevated expression of GPC1 has been reported in breast cancer, glioblastoma and pancreatic cancer . Expression levels of GPC1 have not, however, been evaluated in uterine cervical cancer.…”
mentioning
confidence: 99%
“…Elevated expression of GPC1 has been reported in breast cancer, glioblastoma and pancreatic cancer. [19][20][21][22][23] Expression levels of GPC1 have not, however, been evaluated in uterine cervical cancer.…”
mentioning
confidence: 99%
“…Regarding the MMPs, we were able to verify that GPC1 was positively correlated with MMP expression, which may reveal a role of the PG in GBM invasiveness. It has been suggested that MMP9 could bind to GPCs and possibly with GPC1 [17,31]. Nevertheless, there is no data on whether GPCs could influence MMP2 expression nor a more thorough description of how these expressions would be altered in different kinds of cancer, such as GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Glypican-1 (GPC1) is, along with other GPCs, bound to the membrane through a glycosylphosphatidylinositol (GPI) anchor [9]. It is ubiquitous and influences cellcell and cell-matrix adhesion, metastasis, invasion, and proliferation in various tumors, such as breast, pancreatic, and esophageal cancers [10][11][12][13][14][15][16][17][18]. Although GPC1 has received little focus in regard to glioblastoma, Saito & colleagues demonstrated how this molecule influences the lower survival of GBM patients [19].…”
Section: Research Paper Wwwoncotargetcommentioning
confidence: 99%